Prevalence and Predictors of Elevated Pulmonary Artery Pressure in Nigerian Children with Sickle Cell Anaemia - Usman Muhammad Sani; Usman Muhammad Waziri; Nma M. Jiya; Hamidu Ahmed; Khadijat Omeneke Isezuo; Bilkisu Ilah Garba (Archives of Current Research International, 2020)
Background: Sickle Cell Anaemia (SCA) is the most common inherited disorder in Nigeria. Pulmonary Hypertension (PH) is a known complication of SCA that commences from childhood and progresses as they grow older. Aim: To determine the prevalence and predictors of elevated pulmonary artery pressure (PAP) in children with SCA. Study Design: This is an analytical cross-sectional study. Methods: Three hundred subjects with SCA in steady state and 300 HbAA controls, aged 6 months – 15 years, were enrolled into the study. Children with SCA were recruited by simple random sampling, from the Paediatric Sickle Cell Clinic, Usmanu Danfodiyo University Teaching Hospital, Sokoto. All the children had clinical evaluation, echocardiography, full blood count and reticulocyte count. Pulmonary artery systolic pressure (PASP) and mean pulmonary artery pressure (MPAP) were determined by measurement of tricuspid regurgitant velocity (TRV) and mean gradient (MG) respectively. Results: Seventy-two children with SCA (24.0%) had elevated PAP (defined as TRV ≥ 2.5 m /s) while only 9 (3.0%) had pulmonary hypertension (defined as MPAP ≥ 25 mmHg). Older age (O.R = 1.03, p < 0.001), high systolic blood pressure (O.R = 1.2, p = 0.01), and high reticulocyte count (O.R = 1.33, p = 0.04) were weakly associated with increased likelihood of elevated PAP. Normal pulse oxygen saturation (SPO2 ≥ 95%, O.R = 0.4, p = 0.002) and normal heart sounds on auscultation (O.R = 0.2, p = 0.04) were associated with a reduced likelihood of elevated PAP. Presence of left parasternal heave (O.R = 8.4, p = 0.001) significantly predicted elevated PAP in children with SCA. Conclusion: PH occurs as a complication in children with SCA and certain clinical and laboratory parameters do predict this complication in children.